2017
DOI: 10.4155/tde-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Oral Peptide delivery: Lessons Learnt From the Clinic and Future Prospects

Abstract: Therapeutic peptides have become very successful drugs due to their specificity, potency and low toxicity, but they show challenges for their delivery, due to their short half-life and rapid plasma clearance. For these reasons, peptides are usually administered using injectable sustained-release formulations. Oral peptide route is highly compelling from a patient and commercial point of view. However, poor peptide stability and low permeability across the intestinal epithelium still make it very challenging to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 98 publications
0
25
0
Order By: Relevance
“…Upon pH increase in the intestine, the acid-base reaction creates CO 2 that inflates the balloon, which in turn pushes the microneedles into the intestinal wall to release the peptides. [18,22] A simpler formulation based on the generation of CO 2 to enhance protein absorption was already presented in 2009 under the name of Gas Empowered Drug Delivery (GEDD). [39] This initial system consisted of a cellulose acetate phthalate (CAP)-coated tablet containing citric acid and Na-bicarbonate (for CO 2 production), Ac-Di-Sol as super-disintegrant, poly(ethyleneoxide) (PEO), and the permeation enhancer trimethyl chitosan (TMC).…”
Section: Intestinal Protein and Peptide Systemic Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Upon pH increase in the intestine, the acid-base reaction creates CO 2 that inflates the balloon, which in turn pushes the microneedles into the intestinal wall to release the peptides. [18,22] A simpler formulation based on the generation of CO 2 to enhance protein absorption was already presented in 2009 under the name of Gas Empowered Drug Delivery (GEDD). [39] This initial system consisted of a cellulose acetate phthalate (CAP)-coated tablet containing citric acid and Na-bicarbonate (for CO 2 production), Ac-Di-Sol as super-disintegrant, poly(ethyleneoxide) (PEO), and the permeation enhancer trimethyl chitosan (TMC).…”
Section: Intestinal Protein and Peptide Systemic Deliverymentioning
confidence: 99%
“…However, it is not exempt from hurdles to drug delivery such as variable gastric emptying,13 degradative enzymes,11 complex media composition influencing colloidal stability and drug dissolution,14 a protective mucus layer15 underlying the epithelium, and the intestinal epithelium itself ( Figure ). Once a drug compound, or its loading carrier reaches the intestinal epithelium, four general pathways are identified as potential absorption routes;16 i) transcellular pathway through epithelial cells; ii) paracellular pathway in between adjacent cells; iii) transcytosis and receptor‐mediated endocytosis, typically through either the hydrogen‐coupled peptide transporter (PEOT1), transferring receptor (TfR), IgG neonatal receptor (IgG‐FcRn), or through the vitamin B12 uptake pathway;17,18 iv) lymphatic absorption through M‐cells of Peyer's patches, typically limited to antigen drugs. In addition, upon effective interaction with the epithelium, further mechanisms may decrease the available active dose delivered.…”
Section: Biological Barriers For the Oral Delivery Of Biological Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…[38][39][40][41][42] However, the use of peptides as drugs is limited because of several pharmacokinetic disadvantages (for example, protease-induced degradation). [43][44][45] Although in vitro biological evaluation of HSA-28D showed promising results, we tried to take this project even further; various novel peptidomimetic scaffolds of HSA-28 were designed, synthesized, and conjugated to the surface of PAMAM. Peptidomimetics are compounds whose chemical moieties mimic the 3D structure of natural peptides and retain the ability to bind to biological targets, but without the disadvantages of peptides.…”
Section: Introductionmentioning
confidence: 99%
“…Following ingestion, translocation of particles into and across the GIT mucosa can occur via four mechanisms: 1) endocytosis, through enterocytes, 2) the M-cell-rich layer of Peyer's patches (small-intestine lymphoid aggregates), 3) persorption, where particles can translocate through a "hole" left in the epithelium when enterocytes shed from the villous tip, and 4) the paracellular route, where NPs pass through weakened tight junctions of the epithelial cell layer. [17][18][19][20] Moreover, NP translocation and interactions with tissues in the GIT can be influenced by size, morphology, hydrophilic-hydrophobic balance, and surface functionalization of the particles in question. For example, it has been suggested that negatively charged materials exhibit poor bioavailability, due to electrostatic repulsion and mucus entrapment.…”
Section: Introductionmentioning
confidence: 99%